Impact of Climate, Phenology, and Soil Factors on Net Ecosystem Productivity in Zoigê Alpine Grassland - Rui Qu; Zhengwei He; Li He; Joseph Awange; Yongze Song; Bing Wang; Bo Wen; Jiao Hu (Agronomy)
Net ecosystem productivity (NEP) is a crucial metric for quantifying carbon storage, exchange, and cycling across global atmospheric and terrestrial ecosystems. This study examines the spatiotemporal patterns of NEP in China’s Zoigê alpine grassland and its response to climate variability, phenological changes, and soil conditions from 2000 to 2020. The results show a statistically significant increase in the annual NEP of the Zoigê Plateau, with an average rate of 3.18 g C/m2/year. Spatially, NEP displays strong heterogeneity, with higher values in the southwestern and northeastern marginal areas (>80 g C/m2) and lower values in the central region (<0 g C/m2). In alpine meadows (standardized total effect coefficient [STEC] = 0.52) and alpine steppes (STEC = 0.43), NEP is primarily regulated by soil moisture modulation, influenced by both water and temperature factors. This study accurately assesses NEP by incorporating regional soil characteristics, providing a more precise evaluation of changes in vegetation carbon sink sources in high-altitude areas.